Identifikasi Potensi dan Penerapan Prinsip Sustainable Neighbourhood pada Kawasan Sungai Krueng Daroy, Gampong Peuniti, Banda Aceh - Meutia (Bayt ElHikmah: Journal of Islamic Architecture and Locality, 2025)
The Krueng Daroy River corridor in Gampong Peuniti possesses significant ecological, social, and cultural assets, yet its environmental quality has declined due to domestic wastewater pollution and weak integrated management. This study analyzes the potential application of sustainable neighbourhood principles using a qualitative approachthrough field observations and interviews, based on an analytical framework of urban ecology, water and waste management, community, economy, culture, and operational management. The findings identify key opportunities, including integration with the municipal wastewater system, revitalization of the river corridor as an ecological public space, strengthening culture-based creative economy, and establishing collaborative area governance.